Stability Analysis of Lotka-Volterra Model in The Case of Interaction of Local Religion and Official Religion - Hidayati, Tri; Kurniawan, Wiwit (CV. Inara, 2021)
The purpose of this research is to examine the interaction of local religions and official religions using the Lotka Volterra equation model. This study uses a literature study, which means that all the material in this study is taken, collected and compiled from various existing book sources. The steps in this study are to find the equilibrium point of each equation, then examine the behavior of each equilibrium point obtained. In this study, an analytical study of the prey population model has three equilibrium points, namely and . The stability of the interaction between local religions and official religions is achieved at an equilibrium . From this it shows that the interaction of official religion and local religion does not necessarily lead to the extinction of a religion. The interaction of local religious and official religion there is a point of equilibrium, where the social reality they can work in harmony.